Study on chemical structure stability and properties of chitosan-incorporated tamarind seed kernel xyloglucan hydrogels - Manamoongmongkol, Kanjana; Sriprom, Pongsert; Narkrugsa, Woatthichai; Phumjan, Lamphung; Permana, Lasuardi; Kaewbutra, Sasalux; Assawasaengrat, Pornsawan (My University, 2024)
This study investigated the stability of chitosan-incorporated tamarind seed kernel xyloglucan hydrogels prepared at different ratios after storage for three years. The physical hydrogel samples were studied using ratios of xyloglucan to chitosan between 1.5:1 and 4:1, comparing fresh hydrogel with hydrogel stored for three years. The hydrogels were analyzed for Fourier transform infrared characteristics, rheological behavior, flow rate, and zeta potential. After three years of storage, a reversible reaction was confirmed by C-H molecular stretching using Fourier transform infrared. All hydrogel samples exhibited pseudoplastic fluid characteristics with liquid-like behavior. The zeta potential of fresh hydrogel at 1.5:1 and 4:1 ratios was 27.700 ± 0.964 mV and 22.633 ± 0.929 mV, respectively, whereas after three years, it became 28.067 ± 1.106 mV and 18.867 ± 0.503 mV, respectively. The amount of xyloglucan significantly affected the zeta potential of the xyloglucan-chitosan hydrogel, leading to a decrease in the stability of the hydrogel at a 4:1 ratio. The stability of the hydrogel at a ratio of 1.5:1 was confirmed by pH and zeta potential measurements. In conclusion, the properties and behavior of the xyloglucan-chitosan hydrogel remained stable after three years of storage at a 1.5:1 ratio.
Keywords: Chitosan; Hydrogel; Stability; Storage time; Xyloglucan